Abasto urbano y economía en San Miguel de Tucumán a fines del siglo XVIII y comienzos del XIX. Los criterios de antiguo régimen - Romina Zamora (Nuevo mundo - Mundos Nuevos, 2011)
In this presentation, we analize the inclusion of San Miguel de Tucumán economy in the Andean area according to a regional circulation and the importance in the discussion chapter, the privileges granted by the “cabildo” to “vecinos” based on their industry and trade and those granted by the king to the cities. Second, observe the forms of circulation and exchange of people and goods between the city and the campaign. Third, the production, circulation and labor in the city itself, noting the organization of domestic labor, craft workshops, street trading, trade with merchants of other cities and “conchabo” required. A reading of the sources shows the centrality of the “casa grande” or “casa poblada” in the urban organization and the preeminence of moral values of the city's economy in relation to the supply and circulation of goods, which the council sought logic protect yet the late eighteenth century, when a liberal transformation was taking place, in the way of thinking about economic and political relations within the Spanish monarchy.